The effect of various herbs and packaging material on antioxidant activity and colour parameters of whey (Lor) cheese. (31st March 2021) - Akan, Ecem; Yerlikaya, Oktay; Akpinar, Asli; Karagozlu, Cem; Kinik, Ozer; Uysal, Harun Rasit
Abstract : This study aimed to research the effects of some herbs and the packaging material on total phenolic compound content and the antioxidant activity of Lor cheeses. The total phenolic content and antioxidant activity of Lor cheeses containing only black cumin were found to be significantly lower than cheeses containing black cumin and rosemary or black cumin and thyme ( P  < 0.05). 2, 2‐azino‐di‐(3‐ethylbenzothialozine‐ sulfonic acid) (ABTS) and Cupric Ion Reducing Antioxidant Capacity (CUPRAC) methods were found to be more reliable than the 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) method in evaluating the antioxidant activity of herbs added to Lor cheeses. It has been observed that the packaging material effects the antioxidant activity of the samples differently during the storage. Abstract : Production of whey (Lor) cheese.